The systematic seed anatomy of the meliaceae - with particular reference to the seed-coat of the melioideae - Cheek, M (1989)
Detailed and original descriptions and illustrations of the seed anatomy (especially that of the seed-coat) are presented of the tribes Turraeeae, Melieae, Trichilieae, Guareeae and Sandoriceae. Homologies of the seed-coat strata are established as far as possible, the taxonomic utility of each of the many characters assessed for each tribe and the taxonomic implications gauged using Pennington and Styles’ (1975) generic monograph of the Meliaceae as a basis. Seed-coat characters seem particularly useful in several cases of generic delimitation and show great promise at the infra-generic level, their characters being relatively constant at the species level, but showing great variation between species. At the tribal level, they seem to be of less use in delimitation than do morphological characters but, nevertheless, do give an indication of affinities. Particular attention is paid to the systematic anatomy of 'arillate' and 'sarcotestal' seeds in the Meliaceae and an attempt is made to establish a nomenclatural basis for fleshy seed types in the family. The phylogenetic implications of seed-coat characters are discussed at length on a generic and tribal basis and the functional significance of fruit and seed anatomical characters examined as far as is possible.